Wage and working condition of call center agents in APAC Customer Services Inc., Palo, Leyte. - Acedillo, Rodalyn (Rodalyn Acedillo [and] Chenzi May D. Uy, 2010)
The Business Process Outsourcing (BPO) industry, especially the contact or call centers, is indeed a saving grace to the increasing rate of unemployment in the Philippines. This study proved the following: (1) that even the semi-professional workers or the undergraduates (with good communication and interpersonal skills) are employed in call centers; (2) the main reason why the professional and semi-professional workers like to work in call centers is the high starting salary given to them; (3) call center agents in APAC receive wages according to provincial rates which is relatively lower than the wage rates in call centers outside Leyte, and that these agents are not satisfied with their salary; (4) working in a call center is highly stressful and is detrimental to the health of the workers; (5) even though initial salary is high in call centers, it cannot compensate for the stressful nature of work; and, (6) however stressful their working condition is, the agents are still satisfied with their work (i.e., they gain experience for career growth). Finally, like any other companies, public or private, the employees or workers should be given value and importance, because without them the company will not survive on its own. Employees must be given the wage and benefits they deserve.